Training on Statistical Data Processing Using SPSS Application: Pelatihan Pengolahan Data Statistik Dengan Menggunakan Aplikasi SPSS - Mahariani, Yeni Roha; Suseno, Pangki; Febriansyah, Muhammad Ikhwan (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
The Industry 4.0 era requires resources equipped with critical thinking, innovative abilities, and the capacity to address complex problems using the latest technology. Education emerges as a crucial factor in meeting Human Resources (HR) needs across various industrial sectors. Therefore, this community service activity focuses on students to enhance insights and competencies that support lectures and research projects. The training places emphasis on utilizing the Statistical Package for the Social Sciences (SPSS) as a statistical testing tool, enabling students to grasp accurate data processing. Activities encompass the introduction of basic statistical concepts, practice in data processing, statistical testing, and both descriptive and comparative analysis. The training offers additional experience, skills, and competencies, fostering participants' interaction with SPSS technology as a statistical analysis tool. Evaluation of the activities indicates a significant improvement in participants' ability to process statistical data using SPSS. AbstrakEra Industri 4.0 menuntut sumber daya yang memiliki kemampuan berpikir kritis, inovatif, dan mampu menyelesaikan masalah kompleks dengan memanfaatkan teknologi terkini. Pendidikan menjadi kunci penting dalam memenuhi kebutuhan Sumber Daya Manusia (SDM) di berbagai sektor industri. Oleh karena itu, kegiatan pengabdian ini difokuskan pada mahasiswa untuk meningkatkan wawasan dan kompetensi yang mendukung perkuliahan serta proyek penelitian. Pelatihan menitikberatkan pada penggunaan Statistical Package for the Social Sciences (SPSS) sebagai alat uji statistik, memungkinkan mahasiswa memahami pengolahan data secara tepat. Kegiatan ini mencakup pengenalan konsep dasar statistika, praktik pengolahan data, uji statistik, analisis deskriptif, asosiatif, dan komparatif. Pelatihan memberikan pengalaman, keterampilan, dan kompetensi tambahan, mendukung interaksi peserta dengan teknologi SPSS sebagai alat analisis statistik. Evaluasi kegiatan menunjukkan peningkatan signifikan dalam kemampuan peserta dalam mengolah data statistik dengan SPSS.